In-depth transcriptome profiling of Cherry Valley duck lungs exposed to chronic heat stress - Liu, Yi; Sun, Dongyue; Xu, Congcong; Liu, Xiaoyong; Tang, Min; Ying, Shijia (Frontiers in Veterinary Science, 2024)
Amidst rising global temperatures, chronic heat stress (CHS) is increasingly problematic for the poultry industry. While mammalian CHS responses are well-studied, avian-specific research is lacking. This study uses in-depth transcriptome sequencing to evaluate the pulmonary response of Cherry Valley Ducks to CHS at ambient temperatures of 20℃ and a heat-stressed 29℃. We detailed the CHS-induced gene expression changes, encompassing mRNAs, lncRNAs, and miRNAs. Through protein-protein interaction network analysis, we identified central genes involved in the heat stress response-TLR7, IGF1, MAP3K1, CIITA, LCP2, PRKCB, and PLCB2. Subsequent functional enrichment analysis of the differentially expressed genes and RNA targets revealed significant engagement in immune responses and regulatory processes. KEGG pathway analysis underscored crucial immune pathways, specifically those related to intestinal IgA production and Toll-like receptor signaling, as well as Salmonella infection and calcium signaling pathways. Importantly, we determined six miRNAs-miR-146, miR-217, miR-29a-3p, miR-10926, miR-146b-5p, and miR-17-1-3p-as potential key regulators within the ceRNA network. These findings enhance our comprehension of the physiological adaptation of ducks to CHS and may provide a foundation for developing strategies to improve duck production under thermal stress.